Determination of the carbon dioxide sequestration potential of a nickel mine mixed dump through leaching tests - Razote, Bernard Jomari B. (Animo Repository, 2019)
Carbon dioxide sequestration via mineralization is one of the methods that has the capability to efficiently store carbon dioxide in a stable form. A mixed dump sample collected from a nickel laterite mine in Southern Philippines was tested for its carbon dioxide sequestration potential through HCl leaching tests, employing the Face-Centered Cube (FCC) experimental design for Response Surface Methodology (RSM). Mineralogical analysis performed through X-ray diffraction (XRD) analysis suggests the presence of three minerals, namely goethite, khademite and lizardite; additional X-ray fluorescence (XRF) and inductively-coupled plasma optical emission spectroscopy (ICP-OES) results, however, established goethite as the main component due to the dominance of iron in the sample. Morphological analyses performed through a scanning electron microscope (SEM) and the Brunauer–Emmett–Teller (BET) method suggest high accessible surface area despite considerable variability in sample composition. Leaching tests further confirmed the high reactivity of the mixed dump as high extraction rates were obtained for iron, with the maximum iron extraction efficiency of 95.37% reported at 100 ◦C, 2.5 M, and 2.5 h. The carbon dioxide sequestration potential of the mixed dump was reported as the amount of CO2 that can be sequestered per amount of sample, which was calculated to be 327.2 mg CO2/g sample using the maximum iron extraction obtained experimentally. © 2019 by the authors.